Knowledge economy and modern growth theory - Karim Salem Al-Ghalibi; Ibrahim Rasul Hani (Iraqi Journal for Administrative Sciences, 2024)
The important changes taking place in our world today pose many challenges and opportunities. The information revolution, electronic communications, and the globalization of services bring about an increase in international competition at various levels. The importance of knowledge in the economy is also increasing, until it has become the characteristic of the twenty-first century, the characteristic of the knowledge-based economy. (Knowledge-Based) as knowledge enters as a more basic element than the development of all production and service sectors, as it has become the most important factor in the process of economic growth, unlike classical new theories, which believed that the competitive process in the presence of traditional factors (work and capital) Money (underlies all the motives for progress. This trend in the economy, which is based on the production of goods and services based on material to goods and services based on knowledge, leads to a change in production and marketing processes. The research is based on the hypothesis that (the shift towards a knowledge-based economy will contribute to creating opportunities for economic growth that are relatively unlimited).